Food security in Yemen: An Update - Breisinger, Clemens (2013)
Presentation by Clemens Breisinger, Research Fellow at the International Food Policy Research Institute (IFPRI) at "Consultative and Planning Workshop for Reactivating National Food Security Strategy", September 18-19 in Sana’a, Yemen.